The Effect of Gamification Adoption in Mobile Applications on Consumers' Attitude and Use Intention - (:unkn) unknown (ISTANBUL UNIV, 2018)
With the increasing use of mobile devices in the world and in Turkey, it is possible for companies to reach customers everywhere at any time. For this purpose, mobile applications are prepared by the companies and offered to the consumers. One of the features that has increasing usage in mobile applications is gamification. Gamification is emerging as a new business strategy with innovative applications to increase sales and customer loyalty. The use of gamification and game-based applications helps to ensure a positive experience for consumers. Gamification is providing pleasing experience and increase consumers' loyalty. That's why it is important to examine the effects of gamification on consumer buying behavior. The aim of this study is to determine the effects of gamification acceptance in mobile applications on consumer attitudes and intention to use. As a result of this study, it is determined that gamification in mobile applications influences consumers' attitudes and their intention to use.
Keywords: Gamification; Mobile applications; Attitude; Intention to use; Gamification acceptance; TECHNOLOGY ACCEPTANCE; INTRINSIC MOTIVATION; INFORMATION-SYSTEMS; COMPUTER-TECHNOLOGY; SELF-DETERMINATION; PERCEIVED EASE; INNOVATIVENESS; PLAYFULNESS; SOFTWARE; IMPACT